(untitled) (Bangladesh Journal of Botany, 2021)
Effects of morphological and biochemical constituents on the population of sucking insect pests infesting tomato plant were evaluated. Among the twenty genotypes evaluated under field condition at different seasons (summer, kharif, rabi), it revealed that the genotypes namely BRDT-1, EC 620421, Solanum peruvianum, EC 538455 and S. cheesmaniae had minimum number of aphid and whitefly population throughout all the three seasons due to their morphological traits like more trichome density and thick stem diameter as well as the presence of biochemical attributes like phenol and tannins which were present in those genotypes at higher concentration. The higher content of leaf chlorophyll had resistance effect against the population of aphid and whitefly, while total sugar content did not have any significant effect on resistance. Bangladesh J. Bot. 50(3): 483-489, 2021 (September)